Mapping menstrual health and hygiene progress in US schools: a systematic policy review and comparison across states - Ballard, April M.; Wallace, Emily; Kaza, Pranitha; Self-Brown, Shannon; Freeman, Matthew C.; Caruso, Bethany A. (Frontiers in Reproductive Health, 2025)
IntroductionMenstrual health and hygiene (MHH) policy initiatives have emerged as a key strategy to improve adolescent MHH, particularly through the expansion of state-level legislation aimed at increasing access to menstrual materials in K-12 schools in the United States (US). However, limited research has evaluated the implementation or effectiveness of these policies, and efforts to rigorously track and characterize existing policies remain limited. This study systematically reviewed and characterized state-level policies concerning menstrual material access in K-12 schools.MethodsWe conducted a comprehensive search of all 50 US state government websites and legal databases to identify relevant legislation. Using MHH domains covered by the indicators recommended by the Global MHH Monitoring Group, we characterized policies. We also estimated policy reach by state and overall using National Center for Education Statistics enrollment data.ResultsWe found that 32 (64%) US states have enacted policies since 2017, which have the potential to improve MHH for approximately nine million, or 34%, of K-12 students. Most policies lack comprehensive coverage of essential MHH domains, including only three of the seven MHH domains on average.DiscussionThese findings highlight the need for more rigorous research to evaluate the effectiveness of different policies and identify the best strategies for implementation.